2016
DOI: 10.1093/ije/dyw158
|View full text |Cite
|
Sign up to set email alerts
|

Adult body mass index and risk of ovarian cancer by subtype: a Mendelian randomization study

Abstract: Our data suggest that higher BMI increases risk of non-HGSC, but not the more common and aggressive HGSC subtype, confirming the observational evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 28 publications
7
49
0
3
Order By: Relevance
“…Overall, serous tumors were not associated with an increased risk in either study, however, the OCAC analysis included stratification by tumor grade and found an increased risk for low-grade serous tumors only (OR=1.13 per 5 kg/m 2 ). OCAC confirmed these findings in a later Mendelian randomization study where genetically predicted BMI was associated with an increased risk for non-high-grade serous subtypes only (OR=1.29; 95% CI: 1.03–1.61 per 5 BMI units) and the strongest increase was observed for low-grade serous tumors (OR=1.93; 95% CI: 1.33–2.81) 245 . An increased risk for OC has been observed between waist-to-hip ratio and risk of mucinous tumors (HR per 0.05 unit increment=1.19; 95% CI: 1.02–1.38), but not with serous, endometrioid, or clear cell tumors 240 .…”
Section: Risk Factors and Preventive Factorssupporting
confidence: 58%
“…Overall, serous tumors were not associated with an increased risk in either study, however, the OCAC analysis included stratification by tumor grade and found an increased risk for low-grade serous tumors only (OR=1.13 per 5 kg/m 2 ). OCAC confirmed these findings in a later Mendelian randomization study where genetically predicted BMI was associated with an increased risk for non-high-grade serous subtypes only (OR=1.29; 95% CI: 1.03–1.61 per 5 BMI units) and the strongest increase was observed for low-grade serous tumors (OR=1.93; 95% CI: 1.33–2.81) 245 . An increased risk for OC has been observed between waist-to-hip ratio and risk of mucinous tumors (HR per 0.05 unit increment=1.19; 95% CI: 1.02–1.38), but not with serous, endometrioid, or clear cell tumors 240 .…”
Section: Risk Factors and Preventive Factorssupporting
confidence: 58%
“…Mendelian randomization (MR) is a well-documented application of instrumental variable (IV) methodology using genetic variants (most commonly, single-nucleotide polymorphisms [SNPs]) as IVs to provide relatively unbiased causal estimates of the effect of an exposure (i.e., BMI) on an outcome (i.e., mortality) (14,15). MR has provided evidence to support a causal effect of higher BMI increasing the risk of cardiovascular diseases (CVDs), diabetes, cardiometabolic traits, and various cancers (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, no study has explicitly used MR to explore the causal role of BMI in all-cause and cause-specific mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking is inversely associated with BMI (37) and increased BMI is associated with ovarian cancer (38, 39). Smoking is also widely reported to have anti-estrogenic effects (40) and both endometriosis and ovarian cancer are hormonally related events.…”
Section: Discussionmentioning
confidence: 99%